Autonomization of the legal status of the institute of higher education - Давидова, Наталія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article discusses the sources of university autonomy in Europe. Such basic documents as the Bologna Declaration, Magna Charta Universitatum, Lisbon Declaration, The Declaration on Academic Freedom and Autonomy of Institutions of Higher Education, World Declaration on Higher Education for the Twenty-first Century: Vision and Action, Olvian Declaration are examined. Elements of autonomy Institute of Higher Education are considered: academic, financial, organizational, human resources, scientific autonomy.